Integration of Geometric Motifs from Sumba Ikat Woven Fabricin Didactic Designs for Flat Shape Learning in Elementary Schools - Nabila Muna Mufidah; Risnawati; M. Fikri Hamdani (Journal of Practice Learning and Educational Development, 2026)
Understanding flat shapes remains a challenge for elementary school students, mainly due to the abstract and contextual nature of the material presented. This study aims to develop and evaluate a didactic design for teaching flat shapes by integrating Sumba ikat woven fabric geometric motifs as a contextual medium. The method used was Didactical Design Research (DDR) with stages of design, limited testing, and revision. The research was conducted at SDIT Fadhilah Pekanbaru, involving 30 fourth-grade students as respondents. The instruments used included concept comprehension tests, student worksheets with woven motifs, observations, and semi-structured interviews. The pre-test results showed that around 65% of students had misconceptions about basic geometric shapes. After the intervention, the post-test scores increased by an average of 20%. In addition, interviews showed that the woven motifs made it easier for students to recognize flat shapes that were previously difficult to distinguish. This study concludes that the integration of Sumba ikat weaving geometric motifs into didactic design not only improves cognitive understanding but also encourages affective engagement and appreciation of local culture. This model is relevant to be applied in the context of the Merdeka Curriculum, which emphasizes context-based learning and cultural values.